Nietypowe realizacje jednowymiarowych zmiennych losowych - Heilpern, Stanisław (Untypical realizations of the one-dimensional random variables, 2005)
The paper is devoted to the untypical realizations o f the one-dimensional random variables. This is a review, which presents selected methods o f the detection o f the outliers in univariate data. These are the methods based on the statistical inference or on the graphical methods. They detect the single outliers or the group o f them. The methods used in the normal population case, such as: Dixon’s, Grubbs’ - ordinary and generalized and based on the kurtosis are presented. The method used in the exponential case studied is also. The second part o f the paper is devoted to the methods o f the robust estimation. The paper contains the examples illustrating presented methods and indicates their potential applications. There are four tables with the critical values o f the statistical tests used to the detection o f the outliers in the appendix.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1097, s. 45-67